KOMBINASI TERAPI AUTO STRETCHING DAN ECCENTRIC STRETCHING UNTUK MENURUNKAN DISABILITAS SENDI BAHU PADA TENDINITIS SUPRASPINATUS - Muhammad Untung; Khairul Imam; Herta Meisatama (Universitas Respati Yogyakarta, 2020)
Background: Supraspinatus tendinitis is a inflammation on the supraspinatus tendon because tendon friction in the shoulder bone which is a subacromal narrowing. Objective: This study is intended to prove the impairment of shoulder joint caused of supraspinatus tendinitis by administering a combination of auto stretching and better eccentric stretching from auto stretching and ultrasound. Methods: This study used an experimental design with pre-test design and post-test group. Subjects 28 people with supraspinatus tendinitis. Subjects were divided into 2 groups, ie group I of 14 patients were given a combination of automatic stretch therapy and eccentric stretching 3 times a week for 1 month, while group II of 14 patients were given combination of auto stretching and ultrasound therapy, 3 times a week for 1 month. The measurement of disability degradation test using shoulder pain and disability index (SPADI). Data were analyzed using statistical program for social science (SPSS). Result: Statistical test of paired sample t-test in group I and II obtained p= 0.001 where (p <0,05) There was a decrease of disability. Significant amounts in group I and group II. The result of post-post comparative test with independent t-test shows the value of p = 0,003 (p <0,05). Conclution: The analysis can recognize that there is a significant difference between the two, which is the automatic stretching and better eccentric stretching of automatic stretching and ultrasound in reducing the disability of the shoulder joint due to supraspinatus tendinitis.